+0  
 
0
140
1
avatar+75 

Solve the equation f(x) = -4x^2 - 3x + 2 using the quadratic formula.

gobromash  Apr 27, 2017
Sort: 

1+0 Answers

 #1
avatar+17613 
+1

For  f(x)  =  -4x2 - 3x + 2     a = -4     b = -3     c = 2

The quadratic formula is:  x  = [ -b +/- sqrt( b2 - 4·a·c ) ] / [2·a]

Substituting:                       x  =  [ - -3 +/- sqrt( (-3)2 - 4·(-4)·(2) ) ] / [2·(-4)]

                                            x  =  [ 3 +/- sqrt( 9 + 32 ) / ( -8 )

                                            x  =  [ 3 +/- sqrt( 41 ) ] / -8

                                            x  =  [ -3 +/- sqrt( 41 ) ] / 8

geno3141  Apr 27, 2017

26 Online Users

avatar
avatar
We use cookies to personalise content and ads, to provide social media features and to analyse our traffic. We also share information about your use of our site with our social media, advertising and analytics partners.  See details